A TECHNICAL AND ECONOMIC EVALUATION OF A SMALL SCALE COCONUT OIL EXPELLER OPERATION IN THE COOK ISLANDS - J. C. Barrett T W. Hammonds; R. V. Harris (International Coconut Community Journal, 1987)
Small‑scale processing of copra was demonstrated to be technically feasible and potentially very profitable in the Cook Islands using equipment comprising a copra chopper, a screw press and a filter press. At through‑puts close to 65 kg per hour, yields of ciarified oil and copra cake were around 55 per cent and 40 per cent respectively, on a weight basis. A consumer survey indicated that coconut oil could be marketed as a cooking oil to substitute for imported vegetable oils; potential use in soap manufacture was also identified, while copra cake was readily marketed for animal feeding. For an initial establishment cost of just under NZS 100,000 the f‑mancial internal rate of return for investment in small‑scale copra processing in the Cook Islands, provided that all output can be marketed, is calculated as 49 per cent, which is very attractive. Prospects for the success of similarventures at locations elsewhere in the Pacific are promising.